2019
DOI: 10.1111/iar.12329
|View full text |Cite
|
Sign up to set email alerts
|

Collisional bending of the western Paleo‐Kuril Arc deduced from paleomagnetic analysis and U–Pb age determination

Abstract: The Paleo-Kuril Arc in the eastern Hokkaido region of Japan, the westernmost part of the Kuril Arc in the northwestern Pacific region, shows a tectonic bent structure. This has been interpreted, using paleomagnetic data, to be the result of block rotations in the Paleo-Kuril Arc. To understand the timing and origin of this tectonic bent structure in the Paleo-Kuril arc-trench system, paleomagnetic surveys and U-Pb radiometric dating were conducted in the Paleogene Urahoro Group, which is distributed in the Shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 41 publications
(84 reference statements)
0
32
0
Order By: Relevance
“…Distribution of terranes belonging to the Paleo‐Kuril arc (modified from Katagiri et al, 2019) and paleomagnetic declinations of the terranes with 95% confidence limits (Fujiwara et al, 1995; Fujiwara & Kanamatsu, 1990; Hamano et al, 1986; Nifuku et al, 2009). The Yusenkyo formation was deposited during the late Campanian–early Maastrichtian (Kanamatsu et al, 1992) and the Nakanogawa group during the Paleocene–early Eocene (Nanayama et al, 2019).…”
Section: Overview Of the Paleo‐kuril Arc–trench And Its Tectonic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Distribution of terranes belonging to the Paleo‐Kuril arc (modified from Katagiri et al, 2019) and paleomagnetic declinations of the terranes with 95% confidence limits (Fujiwara et al, 1995; Fujiwara & Kanamatsu, 1990; Hamano et al, 1986; Nifuku et al, 2009). The Yusenkyo formation was deposited during the late Campanian–early Maastrichtian (Kanamatsu et al, 1992) and the Nakanogawa group during the Paleocene–early Eocene (Nanayama et al, 2019).…”
Section: Overview Of the Paleo‐kuril Arc–trench And Its Tectonic Settingmentioning
confidence: 99%
“…The current strikes of the Tokoro Belt (Nikoro and Saroma Groups) and the Yubetsu Group between the Shiranuka and Kitami hills are NNE-SSW to NE-SW, as is the strike of the Nakanogawa Group on the eastern side of the Hidaka Mountains. Paleomagnetic data obtained from the Nemuro Group in the Shiranuka hills and from the Yusenkyo Formation show that the Tokoro and Nemuro Belts were bent clockwise by 90 or more from an initial east-west strike in the original stage of the Kuril arc-trench system (Hamano et al, 1986;Kimura, 1990;Fujiwara & Kanamatsu, 1990;Kanamatsu et al, 1992;Fujiwara et al, 1995;Katagiri et al, 2019; Figure 3). Correcting for this bending requires that the PKA associated with the Olyutorsky arc (OAT in Figure 1) also originally had an east-west to ENE-WSW strike (Hamano et al, 1986;Kimura, 1990;Kanamatsu et al, 1992;Katagiri et al, 2019;Kimura & Tamaki, 1985;Nanayama et al, 1993Nanayama et al, , 2021Vaes et al, 2019; Figure 3).…”
Section: -39mentioning
confidence: 99%
“…The Nemuro Group comprises Upper Cretaceous to middle Eocene forearc basin sediments of the paleo-Kuril arc (Figure 1; Kiminami, 1983;Okada et al, 1987). This group was covered by thick upper Eocene conglomerate of the Urahoro Group (zircon U-Pb age 39 Ma; Katagiri et al, 2019), which contain fan-delta and alluvial-fan facies (Figures 1 and 15b;Nanayama et al, 1994). The conglomerate includes red chert and greenstone clasts derived from the forearc Nikoro Group in the Tokoro belt (Nanayama et al, 1994).…”
Section: Origin Of the Hidaka Continental Crust Related To Ipr Subductionmentioning
confidence: 99%
“…Recently, Katagiri et al (2019) reported U-Pb ages and paleomagnetic measurements for the Nemuro, Urahoro, and Onbetsu groups in the Shiranuka Hills (Figure 1) that provide interesting context to the evolution of the NHB. They showed that the arc-arc collision between the paleo-Kuril and paleo-Japan arcs occurred at the end of the deposition of the Nemuro Group, at approximately 50 Ma.…”
Section: Origin Of the Hidaka Continental Crust Related To Ipr Subductionmentioning
confidence: 99%
See 1 more Smart Citation